2022
DOI: 10.7759/cureus.23517
|View full text |Cite
|
Sign up to set email alerts
|

Neurographic Evidence of Inflammatory Polyneuropathies in Peri-COVID-19 Circumstances and Their Relationship With Acute Disease Severity and Inflammatory Storm

Abstract: Recently, there has been increasing evidence among people infected with coronavirus disease 2019 (COVID-19) of being diagnosed with the typical acute post-infectious inflammatory polyneuroradiculopathy that was formerly known as Guillain-Barré syndrome (GBS), and it is not uncommon that some of them develop chronic inflammatory demyelinating polyneuroradiculopathy (CIDP). However, there is still a large debate and controversy about the link between COVID-19 and polyneuropathy. As a result, a multicentric retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…With the COVID-19 pandemic spread, most of the literature highlights the acute post-infectious polyneuropathy, formerly known as Guillain-Barré syndrome (GBS), as the literature reported a 5.41-fold increase in GBS cases in 2020 compared to 2017-2019 [7]. According to a recent cohort study from Basrah, the prevalence of GBS and chronic inflammatory demyelinating polyneuropathy (CIDP) is six times higher in the COVID-19 population compared to the non-COVID-19 sample [8]. However, mononeuritis multiplex was found in a large proportion of the patients (11 of 69, 16%) with severe COVID-19 admitted to the intensive care units [9].…”
Section: Discussionmentioning
confidence: 99%
“…With the COVID-19 pandemic spread, most of the literature highlights the acute post-infectious polyneuropathy, formerly known as Guillain-Barré syndrome (GBS), as the literature reported a 5.41-fold increase in GBS cases in 2020 compared to 2017-2019 [7]. According to a recent cohort study from Basrah, the prevalence of GBS and chronic inflammatory demyelinating polyneuropathy (CIDP) is six times higher in the COVID-19 population compared to the non-COVID-19 sample [8]. However, mononeuritis multiplex was found in a large proportion of the patients (11 of 69, 16%) with severe COVID-19 admitted to the intensive care units [9].…”
Section: Discussionmentioning
confidence: 99%
“…In 11 studies, a total of 61 GBS cases were reported over 132,132 SARS-CoV-2 hospitalized patients [27,[29][30][31][32][33][34][35][36][37][38]. The modelled proportion yielded 2.96 GBS cases per 1000 SARS-CoV-2 patients (95% CI 0.57; 6.75) (Figure 4a).…”
Section: Incidence Of Gbs In Sars-cov-2 Hospitalized Patientsmentioning
confidence: 99%